3D printed hybrid bone constructs of PCL and dental pulp stem cells loaded GelMA. Issue 12 (25th May 2021) - Buyuksungur, Senem; Hasirci, Vasif; Hasirci, Nesrin
Abstract: Fabrication of scaffolds using polymers and then cell seeding is a routine protocol of tissue engineering applications. Synthetic polymers have adequate mechanical properties to substitute for some bone tissue, but they are generally hydrophobic and have no specific cell recognition sites, which leads to poor cell affinity and adhesion. Some natural polymers, have high cell affinity but are mechanically weak and do not have the strength required as a bone supporting material. In the present study, 3D printed hybrid scaffolds were fabricated using PCL and GelMA carrying dental pulp stem cells (DPSCs), which is printed in the gaps between the PCL struts. This cell loaded GelMA was shown to support osteoinductivity, while the PCL provided mechanical strength needed to mimic the bone tissue. 3D printed PCL/GelMA and GelMA scaffolds were highly stable during 21 days of incubation in PBS. The compressive moduli of the hybrid scaffolds were in the range of the compressive moduli of trabecular bone. DPSCs were homogeneously distributed throughout the entire hydrogel component and exhibited high cell viability in both scaffolds during 21 days of incubation. Upon osteogenic differentiation DPSCs expressed two key matrix proteins, osteopontin and osteocalcin. Alizarin red staining showed mineralized nodules, which demonstrates osteogenic differentiation of DPSCs within GelMA. This construct yielded a very high cell viability, osteogenic differentiation and mineralization comparable to cell culture without compromising mechanical strength suitable for bone tissue engineering applications. Thus, 3D printed, cell loaded PCL/GelMA hybrid scaffolds have a great potential for use in bone tissue engineering applications. Abstract :